On-farm demonstration of improved faba bean varieties in bale and west arsi zones, southeastern oromiya, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
On-farm demonstration of improved faba bean varieties was conducted in Adaba and Dodola districts of West Arsi Zone and Sinana, Goba and Agarfa of Bale Zone. The main objective of the study was to demonstrate and evaluate recently released Aloshe variety along with standard check. The demonstration was under taken on single plot of 10m x 10m area for each variety with the spacing of 40 cm between rows and recommended seed rate of 180 kg ha-1 and fertilizer rate of 100 qt ha-1 NPS. Mini-field day involving different stakeholders was organized at each respective site. Yield data per plot was recorded and analysed using descriptive statistics, while farmers’ preference to the demonstrated varieties was identified using focused group discussion and summarized using pair wise and simple ranking methods. The demonstration result revealed that Aloshe variety performed better than the standard check of Mosisa variety with an average yield of 35.97 qt ha-1, while that of the standard check was 28.50 qt ha-1. Aloshe variety had 26.21% yield advantage over the standard check. This variety was selected by farmers in Adaba, Dodola and Agarfa. Thus, Aloshe variety was recommended for further scaling up in the area it was selected.Int. J. Agril. Res. Innov. Tech. 12(1): 8-11, June 2022